The Effect of Benefit, Ease of Service and Feedback in using the UB-Care Digital Application on the Image of the Institution With Customer Satisfaction (Stakeholder) as Intervening Variable at University of Brawijaya - Ayu Rahardani Winoersita; Ainul Hayat; Tjajanulin Domai (Sekolah Pascasarjana Universitas Brawijaya, 2022)
Problems with the academic community in Indonesia now often involve the wider community, where such actions can injure the integrity of the University as a Higher Education (PT) which has become a formal educational institution in Indonesia. Meanwhile, to manage these problems, which can be done with public service management in accommodating complaints so that they can be resolved in an integrated manner as an embodiment of Good Governance at the university level. The purpose of this study is to evaluate and identify the effect of the UB-Care Application at the University of Brawijaya in managing complaints from stakeholders who have problems, criticisms, and also suggestions related to educational facilities at the University of Brawijaya, wherein this research it involves the existence of the effect of using the UB-Care Application on the perception of utilization, convenience, feedback that can result in customer satisfaction and the end can affect the image of University of Brawijaya itself. The method used in this research is explanatory research or explanation with a quantitative approach using an instrument in the form of a Likert scale questionnaire. The sampling technique is Non-Probity Sampling Purposive Sampling from 100 respondents. The results obtained, namely, the effect of using the UB-Care Application on the perception of utilization, convenience, feedback can affect the image of the University of Brawijaya with the help of customer satisfaction as an intervening variable.